ETHEPHON IN THE ANTECIPATION OF THE HARVEST AND QUALITY OF REUBENNEL PLUMS - FIORAVANÇO, João Caetano; PAIVA, Marília Caleffi; BIZZANI, Ernesto (Scientia Agraria, 2007)
This work was carried out at the Centro de Pesquisa da Região da Serra (FEPAGRO SERRA), in Veranópolis, RS, Brazil, with the objective of evaluating the effect of Ethephon early harvest and postharvest quality of plums cv. Reubennel. The treatments applied were: 1) control; 2) Ethephon (120 mg L-1); 3) Ethephon (240 mg L-1); 4) Ethephon (360 mg L-1); 5) Ethephon (480 mg L-1). Twelve-year-old plum trees were sprayed 15 days before the expected harvest time. The trees were treated with a costal pulverizer, and then applied a spray directly on the fruits. At the moment of application, the plums were completely developed and the skin exhibited a clear green color. The results showed that the use of Ethephon put forward plum harvesting, but didn't influence the flesh firmness, pH and titratable acidity. At the harvest time, plums treated with Ethephon at the rates of 360 and 480 mg L-1 exhibited a more intensified red color skin. The total soluble solids content was higher in the plums not treated with Ethephon.